2020
DOI: 10.1111/exd.14178
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of proangiogenic microvesicles from hypertrophic scar myofibroblasts

Abstract: Hypertrophic scars are a common complication of burn injuries and represent a major challenge in terms of prevention and treatment. These scars are characterized by a supraphysiological vascular density and by the presence of pathological myofibroblasts (Hmyos) displaying a low apoptosis propensity. However, the nature of the association between these two hallmarks of hypertrophic scarring remains largely unexplored. Here, we show that Hmyos produce signalling entities known as microvesicles that significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Communication via micro‐vesicles is also a feature of myofibroblasts. In this issue, Laberge et al 53 report that myofibroblasts derived from human hypertrophic scars shed proangiogenic micro‐vesicles that significantly stimulate proliferation and migration by cultured endothelial cells and promote capillary‐like tube formation.…”
Section: Fibroblast‐adipocyte Connectionmentioning
confidence: 99%
“…Communication via micro‐vesicles is also a feature of myofibroblasts. In this issue, Laberge et al 53 report that myofibroblasts derived from human hypertrophic scars shed proangiogenic micro‐vesicles that significantly stimulate proliferation and migration by cultured endothelial cells and promote capillary‐like tube formation.…”
Section: Fibroblast‐adipocyte Connectionmentioning
confidence: 99%
“…Numerous studies have shown that the degree of scar hyperplasia is closely related to the growth of new blood vessels. , The microcirculation blood flow visualizer and immunohistochemical staining were used to investigate the effect of CSB-NEG on microcirculation of HS tissues. As shown in Figure C, microvessels in the normal skin tissue were clearly visible, with good blood circulation, and no abnormal proliferation of small vessels was observed.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β 1 mainly acts through the TGF-β/Smad signaling pathway. Research showed that the expression of TGF-β 1 , Smad2, and Smad3 increased in the scar tissue S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…88 Another study reported the down-regulation of IL-6, IL-8 and CCL2 but an up-regulation of TNFα and CXCL4 with an augmented presence of M2 macrophages in the scar. 89 Laberge et al 90 have demonstrated that myofibroblasts isolated from hypertrophic scars produce microvesicles that stimulate angiogenesis, sustaining and further amplifying angiogenesis in these pathological scars. Further analysis would thus be necessary to evaluate whether inflammatory and pro-angiogenic mediators influence hypertrophic scarring in the skin in relation to myofibroblast persistence.…”
Section: Myofibroblasts In Hypertrophic Scarsmentioning
confidence: 99%